A DELAY POINT OF VIEW CAUSED BY U-TURNING VEHICLE (CASE STUDY : FOUR U-TURN LOCATION OF ARTERIAL STREETS IN BANDUNG) - M. ALAMSYAH (NIM 25003010); Pembimbing: Ir. Titi Liliani Soedirdjo, M.Sc., dan Ir. Hedi Hidaya, AGUNG
Abstract: At present, serious traffic problems are commonly encountered in Bandung. When moving from one place to another destination the time spend will be long because of traffic jams, at intersection and median opening used as U-Turn by all type of vehicles as well as motorcycles. This study is focusing an the travel delay of vehicles going one way or coming from opposite direction, caused by vehicles doing an U-Turn at median opening. Data collection was done using two video camera to record the vehicles travel time going one way or coming from opposite direction. Location observed were the road segment 6/2 D at Jln. Kiaracondong and Jln. Soekamo Hatta and road segment of 4/2 D at Jln. Pelajar Pejuang45 and Jln. Trs. Buah Batu. The computation, at the four locations of observation include the average vehicles travel time at segment 6/2 D for vehicle doing U-Turn was 11,62/sec -17,88/sec, vehicles not doing U-Turn because affected condition, showed a travel time was 22,11/sec - 36.45/sec; and at not affected condition travel time was 14,56/sec - 28,48/sec. For motorcycles doing U-Turn the average travel time was 9,34/sec - 9,81/sec, motorcycles not doing U-Turn at affected condition showed was 15,72/sec - 19,92/sec; and at not affected condition travel time was 10,81/sec - 15,75/sec. For road segment 4/2 D average travel time of vehicles doing the U-Turn was 23,69/sec - 25,02/sec, vehicles not doing U-Turn at affected condition showed an average travel time was 24,42/sec - 36,49/sec; and at not affected condition the average travel time was 18,44/sec - 29,00/sec. Average travel time for motorcycles doing U-Turn was 12,89/sec - 16,62/sec, the travel time for motorcycles not doing U-Turn at affected condition was 16,45/sec - 25,28/sec; whereas travel time for unaffected condition was 13,24/sec - 19,42/sec. Therefore, delay of vehicles at road segment 6/2 at affected U-Turn condition was 6,22/sec - 20,46/sec; and at unaffected condition was 1,78/sec - 12,94/sec. The travel delay for motorcycles at affected U-Turn condition was 4,17/sec - 8,37/sec; and at unaffected condition was 2,00/sec - 4,69/sec. The delay at road segment 4/2 D for vehicles showed at affected condition was 5,56/sec - 15,84sec; and at unaffected condition was 5,13/sec - 10,14/sec. Whereas, for motorcycles at affected condition travel time showed was 2,40/sec - 12,04/sec; and at unaffected condition was 3,57/sec - 5,37/sec. The average travel time computation result at road segment 6/2 D and 4/2 D for vehicles and motorcycles influenced by condition like the number of lane, width of median opening, type of pavement and type of vehicles or motorcycles, at observation location provided a conclusion that condition is mostly influence by the number of lane and width of median opening. For vehicles and motorcycles doing U-Turn was 9,34/sec - 25,02/sec; and for vehicles and motorcycles not doing U-Turn travel time was 10,81/sec - 36,45/sec. Travel delay of vehicles and motorcycles was 1,78/sec - 20,46/sec, such condition is influenced also by the number of lane and width of median opening at location.